History Learning Module Based on Islamic Values on K.H. Hasyim Asy’ari’s Jihad Resolution Material - Fadli, Muhammad Rijal; Sudrajat, Ajat (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
The purpose of this study was to produce a feasible module. Islamic values-based learning module is an innovation to support educational progress. This module could be utilized as teaching materials to shape the student's religious character through independent learning to achieve the desired competency goals. The research method used was the R&D (Research and Development) with the ADDIE procedure as the development model. The data were collected through observation, interviews, and questionnaires. The results showed that the developed module was feasible based on the feasibility assessment by material experts, media experts, teachers, and students. Overall, it met the feasibility criteria with an average score of 4.75 from the material experts, 4.55 from the media experts, 4.28 from the teachers, 4.45 from the limited rial, and 4.61 from the field trial. The module was declared feasible, effective, and practical to be used as teaching materials and learning resources by students in the history learning process. The benefit is that the material in the module is integrated with Islamic values to improve and shape the students’ religious character.